Definition of a High-Resolution Molecular Marker for Tracking the Genetic Diversity of the Harmful Algal Species Eucampia zodiacus Through Comparative Analysis of Mitochondrial Genomes - Zhang, Mengjia; Cui, Zongmei; Liu, Feng; Chen, Nansheng (Frontiers in Microbiology, 2021)
The cosmopolitan phytoplankton species Eucampia zodiacus is a common harmful algal bloom (HAB) species that have been found to cause HABs in essentially all coastal regions except the Polar regions. However, molecular information for this HAB species is limited with only a few representative molecular markers. In this project, we constructed the mitochondrial genome of E. zodiacus, which was also the first mitochondrial genome constructed for any species in the order Hemiaulales that includes 145 annotated species (including two HAB species Cerataulina bicornis and Cerataulina pelagica). Comparative analysis of common molecular markers revealed low genetic divergence. However, we could distinguish different E. zodiacus strains using whole mitochondrial genomes, suggesting evolutionary divergence of E. zodiacus strains. Through comparative analysis of multiple E. zodiacus strains, we identified a new molecular marker ezmt1 that could adequately distinguish different E. zodiacus strains isolated in various coastal regions in China. This molecular marker ezmtl could be an effective molecular marker for tracking causative strain in E. zodiacus HABs, which will be effective in identifying the causative strains during E. zodiacus HABs.